Non-contact high resolution microwave scanning measurement technology - SHVETS, IGOR (IEEE, 2003)
For non-contact inspection of microwave integrated and hybrid circuits a technical concept and realisation of a high resolution scanning technique for the detection of the electric field distribution has been developed. The near-field signal is measured in magnitude and phase allowing the calculation of the signal flow in the device under test.
PUBLISHED
Keywords: Particles and fields physics; near-field signal